The loyal 47 ronin [videorecording (DVD)] Chūshingura - Hasegawa, Kazuo, 1908-1984; Katsu, Shintarō, 1931-1997; Ichikawa, Raizō, 1931-1969; Tsuruta, Kōji, 1924-1987; Watanabe, Kunio, 1899-1981; Watanabe, Kunio, 1899-1981 (Samurai cinema., 2009)
A timeless tale of honor and revenge. The true story of a group of samurai who become ronin after their lord is forced to commit seppuku for assaulting a court official.